STAD COOPERATIVE LEARNING WITH WORKSHEETS FOR MATHEMATICAL PROBLEM SOLVING IN A NUMERACY CONTEXT - Rustam Effendy Simamora; Rika Diyah Maulana; Setia Widia Rahayu (Department of Mathematics Education Universitas Borneo Tarakan, 2025)
This study examined the effect of Student Teams Achievement Divisions (STAD) cooperative learning supported by student worksheets on seventh-grade students’ mathematical problem-solving ability (MPSA) in a numeracy context. A quasi-experimental non-equivalent control group pretest–posttest design was used, with one class assigned as the experimental group and another as the control group. Data were collected using essay-type pretest and posttest instruments scored using four indicators derived from Pólya’s problem-solving framework: understanding the problem, devising a plan, carrying out the plan, and looking back. Data were analysed using descriptive statistics and analysis of covariance (ANCOVA), with pretest scores treated as a covariate. ANCOVA results showed a significant effect of instructional group on posttest MPSA after controlling for initial ability, and the pretest covariate significantly predicted posttest performance. Indicator-level ANCOVA indicated that the strongest group differences occurred in understanding the problem and devising a plan, while no significant difference was found for carrying out and checking the solution. These findings suggest that STAD supported by worksheets contributes particularly to students’ early-stage problem-solving processes in numeracy-oriented mathematics learning. Results should be interpreted cautiously due to the non-randomized design and limited number of test items. Keywords: cooperative learning, numeracy, problem-solving, student teams achievement divisions, worksheet. Penelitian ini mengkaji pengaruh pembelajaran kooperatif tipe Student Teams Achievement Divisions (STAD) yang didukung lembar kerja siswa terhadap kemampuan pemecahan masalah matematis (KPMM) siswa kelas VII dalam konteks numerasi. Penelitian menggunakan desain kuasi-eksperimen non-equivalent control group pretest–posttest, dengan satu kelas sebagai kelompok eksperimen dan satu kelas sebagai kelompok kontrol. Data dikumpulkan melalui tes uraian pretest dan posttest yang dinilai menggunakan empat indikator yang diturunkan dari kerangka pemecahan masalah Pólya, yaitu memahami masalah, menyusun rencana penyelesaian, melaksanakan rencana, dan memeriksa kembali penyelesaian. Analisis data dilakukan dengan statistik deskriptif dan analisis kovarians (ANCOVA) dengan skor pretest sebagai kovariat. Hasil ANCOVA menunjukkan adanya pengaruh signifikan kelompok pembelajaran terhadap skor postest KPMM setelah mengontrol kemampuan awal, dan skor pretest berkontribusi signifikan dalam memprediksi skor postest. Analisis ANCOVA per indikator menunjukkan perbedaan paling kuat pada indikator memahami masalah dan merencanakan penyelesaian, sedangkan pada indikator melaksanakan dan memeriksa kembali penyelesaian tidak ditemukan perbedaan signifikan. Temuan ini mengindikasikan STAD berbantuan lembar kerja terutama mendukung tahapan awal proses pemecahan masalah dalam pembelajaran matematika berbasis numerasi. Hasil perlu ditafsirkan hati-hati karena desain non-random dan jumlah butir soal terbatas. Kata kunci: kemampuan pemecahan masalah, lembar kerja siswa, numerasi, pembelajaran kooperatif, student teams achievement divisions.